The impact of marketing on Activities of Vietnam Arts and Cultural Organizations - Nguyễn, Thị Anh Quyên (2023)
With the trend of budget reduction and autonomous operation of arts and cultural organizations, competition in this field to attract audiences is an inevitable trend. This sets out the requirements of marketing activities to bring arts to the audiences and bring the audience to arts, which is, to link arts with the audience; not only achieved the goal of establishing and meeting the audience needs, but also fulfilled the arts and cultural organizations' task of creating arts. There have been many research perspectives on culture and arts marketing in the context of cultural integration and economic development associated with the characteristics of each country and region. In this study, the author approaches, inherits, and develops Rentschler's culture and arts marketing model to build a scale and conduct practical research in Hanoi, Vietnam. The survey subjects were identified as art practitioners (artists) with more than 3 years of working experience in 7 theaters in Hanoi. The research was carried out by qualitative method through secondary data collection, combined with the quantitative method through a survey of opinions of 200 artists.